2014
DOI: 10.1371/journal.pone.0114510
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cyclopamine and Tamoxifen Promotes Survival and Migration of MCF-7 Breast Cancer Cells – Interaction of Hedgehog-Gli and Estrogen Receptor Signaling Pathways

Abstract: Hedgehog-Gli (Hh-Gli) signaling pathway is one of the new molecular targets found upregulated in breast tumors. Estrogen receptor alpha (ERα) signaling has a key role in the development of hormone-dependent breast cancer. We aimed to investigate the effects of inhibiting both pathways simultaneously on breast cancer cell survival and the potential interactions between these two signaling pathways. ER-positive MCF-7 cells show decreased viability after treatment with cyclopamine, a Hh-Gli pathway inhibitor, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…Exogenous SHH stimulation shows no direct effect on gene expression of Hedgehog pathway genes, but it positively affects the migratory potential of the cells. It is possible that the SHH ligand binds to an alternative target and stimulates cell migration, as we have shown recently on breast cancer (42), and this effect should be investigated further. Endogenous stimulation of the pathway by GLI1 results in upregulation of PTCH1 and GLI2/3.…”
Section: Discussionmentioning
confidence: 90%
“…Exogenous SHH stimulation shows no direct effect on gene expression of Hedgehog pathway genes, but it positively affects the migratory potential of the cells. It is possible that the SHH ligand binds to an alternative target and stimulates cell migration, as we have shown recently on breast cancer (42), and this effect should be investigated further. Endogenous stimulation of the pathway by GLI1 results in upregulation of PTCH1 and GLI2/3.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that the Hh signaling pathway participates in various tumor processes, including formation, development, metastasis and angiogenesis (38)(39)(40). In the present study, the expression of the molecules involved in the Hh signaling pathway was investigated, and the results revealed that GLI1, PTCH1, SMO and SHh were overexpressed in cervical cancer tissues (squamous carcinoma vs. normal cervical tissue, all P<0.01; adenocarcinoma vs. normal cervical tissue, P=0.014, P=0.007, P=0.007 and P=0.007, respectively).…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…The widely used hedgehog inhibitor cyclopamine belongs to a group of plant-derived alkaloids, first identified for their teratogenic activity in sheep [ 1 ]. Cyclopamine acts through direct binding to Smo, therefore, inhibiting the downstream canonical Hh signaling pathway [ 69 ]. It has also been shown to inhibit the non-canonical Akt pathway, although the precise mechanism for this is not clear [ 3 , 70 ].…”
Section: Potential Therapeutic Targeting Of the Hedgehog-signalingmentioning
confidence: 99%